Optimalisasi Pemahaman Materi Kisah Nabi melalui Metode Mind Mapping dengan Pendekatan PBL-TPACK - Maulita, Bela Zahra; Khasanah, Nur (Indonesian Journal of Islamic Elementary Education, 2024)
This research was motivated by the low level of students’ understanding of PAI learning material on prophet stories at SD Muhammadiyah 02 Noyontaan. Therefore, this research aims to apply the Mind Mapping learning method and the TPACK integrated PBL approach to optimize students’ understanding in PAI subject material on Prophet’s Stories. The type of research used in this research is classroom action research which consists of three cycles. The target of this research was class III students at SD Muhammadiyah 02 Noyontaan. Based on the research results, the average in the pre-cycle was 74 with a classical completeness percentage of 73.9%, the average student learning outcome in cycle I was 77 with a classical completion percentage of 76.6%, the average student learning outcome in cycle II was 81 with a classical completeness percentage of 85.6% and an average learning outcome for cycle III students of 90 with a classical completeness percentage of 95%. From these data it can be concluded that the Mind Mapping learning method and the TPACK integrated PBL approach are proven to be able to improve learning outcomes for Class III Prophet’s Story material at SD Muhammadiyah 02 Noyontaan.